ICE STORAGE CHARACTERISTICS OF CULTURED MACRO BRACHIUM ROSENBERG II (DE MAN - RODRIGUES, FANITA; BASU, SUBRATA; HAZRA, ANSUMAN (Journal of Indian Fisheries Association, 2016)
CulturedMacrobrachium rosenbergii (Scampi; 30-40 g) in headless shell-onform was stored in ice (Prawn:ice=l:2) in a plywood box insulated with 2 emthick expanded polystyrene and subjected to detailed examination of qualityby chemical, microbiological and organoleptic evaluation at regular intervalsto assess the storage life. The prime quality life of prawns in ice was found tobe 8 days followed by a phase of lowered quality, but still acceptable till theend of 13 days.Keywards : Ice storage characteristics, M. resenbergii, storage life